-2x+5=-1x+1

Simple and best practice solution for -2x+5=-1x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+5=-1x+1 equation:


Simplifying
-2x + 5 = -1x + 1

Reorder the terms:
5 + -2x = -1x + 1

Reorder the terms:
5 + -2x = 1 + -1x

Solving
5 + -2x = 1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
5 + -2x + x = 1 + -1x + x

Combine like terms: -2x + x = -1x
5 + -1x = 1 + -1x + x

Combine like terms: -1x + x = 0
5 + -1x = 1 + 0
5 + -1x = 1

Add '-5' to each side of the equation.
5 + -5 + -1x = 1 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = 1 + -5
-1x = 1 + -5

Combine like terms: 1 + -5 = -4
-1x = -4

Divide each side by '-1'.
x = 4

Simplifying
x = 4

See similar equations:

| 3logx=3.3 | | -1x+1=-12 | | 9/x=63/77 | | 5u+3=33 | | 19x+5y=7 | | 17p^2+16=2151 | | f(x)=x^3-1.5x^2-1 | | N/400=2/100 | | 13p^3-3=4209 | | x^(5/3)=1.10 | | 9(11-k)=3(3k-6) | | 4x^2-x+29=0 | | 4x-2=-4-12x | | 4x-2=-4-12 | | 16pqr^2/2pq^2r | | 6(x-2)/5-3(x+1)/5=2(x-5) | | -3cos(2x)-7cos(X)-5=-7 | | 27x^2-25=0 | | (6x)/(4x) | | Y-10+y=22 | | 6c+5d+3c-2d= | | log(x)/4=-1/2 | | 2x-2=x-7 | | lg(x)/4=-1/2 | | 3(x+12)=24-5x | | 2x+17=x+17 | | Y=120-0.25x | | 5(x-1)-(x+2)=0 | | 7x+8=17-2 | | 11x+4=13x-2 | | 4x+17y=13 | | 2sinx-3cosx-2.5=0 |

Equations solver categories